ANALISIS PENCATATAN AKUNTANSI UMKM PADA TOKO AIS WUNDULAKO - Sastra, Annisa Dea; Turi, La Ode; Chairunnas, Arnadi (Komunitas Manajemen Kompetitif, 2025)
A type of productive business owned by an individual or business entity, with specific criteria based on assets and turnover. This is the general definition of Micro, Small, and Medium Enterprises (UMKM). Based on the data obtained, UMKM can assist the government in driving the production sector. In line with the development of UMKM, the primary focus in managing business funds is to implement proper accounting records. With proper accounting records, UMKM can strengthen their businesses by applying for loans through financial statements that demonstrate their performance and financial position. This study aims to analyze and determine the form of accounting records at Toko Ais. The type of research used is qualitative research with a descriptive approach. Data collection uses observation, interviews, and documentation techniques. The results of this study indicate that Toko Ais UMKM have not implemented accounting records in accordance with accounting standards due to the lack of transaction evidence to record accounting details, where the records only include total cash sales, purchases, personal withdrawals, and other operational costs. This occurs due to a lack of awareness and understanding of the importance of accounting records for a business. Keywords: Accounting Records, UMKM